STRATEGI PENGEMBANGAN AGROINDUSTRI TAHU DI DESA DOLOK MANAMPANG KECAMATAN DOLOK MASIHUL KABUPATEN SERDANG BEDAGAI - Hariance, Rika; Saragih, Ummul Hikmah; Yani, Yulistriani (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Dolok Manampang Village is the largest tofu production center in Serdang Bedagai Regency with 15 industries and 70 variants of derivative products. However, this agroindustry faces challenges in production efficiency, marketing and increasing competitiveness. This study aims to formulate a development strategy for tofu agroindustry in Dolok Manampang Village. This research used a descriptive analysis method with a qualitative approach. Data were collected through interviews, observations, and literature studies. The types of data sources applied in this research are primary data and literature studies. The types of data sources applied in this research are primary data and secondary data. The analysis techniques applied include internal and external environment analysis using the SWOT approach and strategy selection using the QSPM method. The results of the analysis in this study illustrate that the IFE matrix analysis has a total score oe 2,88. This indicates that the tofu agroindustry in Dolok Manampang village has a strong internal position. Furthermore, the EFE matrix has a total score of 2,92. This indicates that the tofu agroindustry in Dolok Manampang village is able to respond well to the opportunities and threats that come. Based on the results of the analysis through the QSPM matrix, the resulting priority strategy is to create a village online platform to market the villages superior products and facilitate business actors with digital marketing training. In addition, it is recommended to create a special page (fanspage) which will facilitate the sale of tofu both information and interesting content about the tofu agroindustry in Dolok Manampang village. With the implementation of this strategy, the tofu agroindustry can become a driving force for sustainable local economic development.